2017
DOI: 10.1016/j.cjca.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction in Cardiology: Pathophysiology, Investigation, and Management

Abstract: Presyncope and syncope are common medical findings, with greater than 40% estimated lifetime prevalence. These conditions are often elicited by postural stress and can be recurrent and accompanied by debilitating symptoms of cerebral hypoperfusion. Therefore, it is critical for physicians to become familiar with diagnosis and treatment of common underlying causes of presyncope and syncope. In some patients, altered postural hemodynamic responses are due to failure of compensatory autonomic nervous system refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 65 publications
(99 reference statements)
1
29
0
3
Order By: Relevance
“…Postural tachycardia syndrome (POTS) is a relatively common circulatory condition, estimated to affect 0.1-1% of the population [1], disproportionately affecting women in the adolescent and young adult age range [1][2][3]. POTS can be associated with a variety of clinical syndromes including myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) [4] and Ehlers-Danlos syndrome [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postural tachycardia syndrome (POTS) is a relatively common circulatory condition, estimated to affect 0.1-1% of the population [1], disproportionately affecting women in the adolescent and young adult age range [1][2][3]. POTS can be associated with a variety of clinical syndromes including myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) [4] and Ehlers-Danlos syndrome [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of POTS requires an exaggerated increase in heart rate (HR) from supine to standing of at least 30 beats per minute for adults (20 years of age or older), or at least 40 bpm for adolescents over the course of 10 min upright, in the absence of orthostatic hypotension during the first 3 min [7]. The diagnosis also requires the presence of chronic orthostatic symptoms such as fatigue, lightheadedness, blurry vision, weakness, cognitive difficulties, and nausea [1][2][3][8][9][10]. Although tilt table testing was the initial method of orthostatic testing in POTS studies [8], in-office passive standing tests (PST), during which the individual leans against a wall [5,11], or active standing tests (without any support) [12][13][14][15] have also been used for several decades.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 1). In our case, the autonomic insufficiency is attributed to the underlying coronary artery disease [1,2], and the CABG surgery has led to its worsening, as shown in the frequency of our patient's syncopal episodes and cardiac pauses postoperatively. The symptomatology of our patient was an overlap of two interconnected conditions, which explains partial improvement with the pacemaker placement to treat the autonomic dysfunction and complete resolution of his symptoms following fludrocortisone use.…”
Section: Discussion and Literature Reviewmentioning
confidence: 55%
“…It is well established that Heart Rate Variability (HRV) is affected by coronary artery disease, namely following a myocardial infarction [1,8]. Studies have also revealed a more pronounced reduction in HRV following cardiac and thoracic surgeries [2,9], yet it was found to be temporary and reversible within 3-6 months from the operation.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation